2017
DOI: 10.1055/s-0043-115007
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Coffee on Health

Abstract: Coffee is one of the most popular and widely consumed beverages worldwide due to its stimulating effects on the central nervous system as well as its taste and aroma. Coffee is a complex mixture of more than 800 volatile compounds whereas caffeine and chlorogenic acids are the most common compounds. During the last years, coffee has progressively moved to a less negative position on health due to its better-known pharmacology. Caffeine, e.g., in a cup of coffee, appears to exert most of its effects through an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
114
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(138 citation statements)
references
References 76 publications
2
114
1
9
Order By: Relevance
“…The biochemistry of coffee and tea has been extensively documented, indicating that different roasting, temperatures, or brewing of the two can impact the abundancy and bioavailability of their complex compounds 6,7 . There has been an ongoing debate as to whether habitual consumption of coffee 8 and tea 9 is beneficial or harmful to health. The conclusion varies among outcomes; lowering the risk for type 2 diabetes and cardiovascular diseases 10,11 , and increasing serum levels of low-density lipoprotein (LDL) and total cholesterol 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biochemistry of coffee and tea has been extensively documented, indicating that different roasting, temperatures, or brewing of the two can impact the abundancy and bioavailability of their complex compounds 6,7 . There has been an ongoing debate as to whether habitual consumption of coffee 8 and tea 9 is beneficial or harmful to health. The conclusion varies among outcomes; lowering the risk for type 2 diabetes and cardiovascular diseases 10,11 , and increasing serum levels of low-density lipoprotein (LDL) and total cholesterol 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion varies among outcomes; lowering the risk for type 2 diabetes and cardiovascular diseases 10,11 , and increasing serum levels of low-density lipoprotein (LDL) and total cholesterol 12 . Given the presence of different compounds in these two beverages with diverse effects on disease risk, observational studies have given rise to contradictory findings, especially regarding coffee consumption 8 . Previous studies, however, have shown a consistent association of coffee consumption with lower risk of overall mortality 13 and liver diseases 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are studies describing a possible association between coffee consumption and increased risk of lung cancer, laryngeal cancer, gastric cancer, endometriosis, rheumatoid arthritis and fracture in women (Table 2). 1,2,[5][6][7][8][9][10] Coffee contains a wide array of compounds, including the major component, caffeine. Caffeine is well-known to be associated with a range of physiological effects, specifically on cardiovascular system.…”
mentioning
confidence: 99%
“…Though, there is a presumed evidence of coffee intake has favorable effects for a variety of conditions. 1,2,[5][6][7][8][9][10] In this review, we will outline contemporary evidencebased knowledge in the context of association of coffee with dermatological diseases, in particular, melanoma/non-melanoma skin cancers, psoriasis and rosacea.…”
mentioning
confidence: 99%
“…9.08 million metric tons in 2015/2016(ICO, 2016. Besides its sensorial properties, brewed coffee is an important source of antioxidants, which play an important role as health protecting factors (Nicoli et al, 1997;Brezová et al, 2009;Nieber, 2017). For instance, consumption of coffee brew (CB) has been linked to reduced risk of death attributed to inflammatory and cardiovascular diseases (Andersen et al, 2006), and to reduced incidence of diabetes and liver disease (Cano-Marquina et al, 2013).…”
mentioning
confidence: 99%